Longitudinal Follow-Up of Choroidal Thickness in Central Retinal Vein Occlusion With and Without Cystoid Macular Edema. (September 2018) - Thompson, Atalie C.; Thomas, Akshay S.; Rothman, Adam L.; Berry, Duncan; Fekrat, Sharon
Purpose: To investigate the longitudinal relationship between subfoveal choroidal thickness (CT) and central retinal vein occlusion (CRVO). Methods: Retrospective cohort of 104 subjects with enhanced-depth imaging optical coherence tomography for unilateral CRVO. Mean CT and best-corrected visual acuity (BCVA) were compared in eyes with and without CRVO and in eyes with CRVO with and without cystoid macular edema (CME). Results: CT was thicker in eyes with CRVO-related CME than uninvolved contralateral eyes at baseline (263.9 ± 86.9 versus 230.2 ± 87.9 µm; P < .001) and final follow-up (261.1 ± 94.7 versus 222.3 ± 86.2 µm; P = .007). CRVO eyes treated with intravitreal antivascular endothelial growth factor with or without steroid therapy showed a significant reduction in CT at final follow-up (256.3 ± 90.7 versus 236.9 ± 85.9 µm; P = .004). Subjects with CRVO who were not treated with intravitreal injections also showed a significant but more modest decline in CT over time (234.4 ± 94.2 versus 221.5 ± 97.1 µm; N = 31; P = .02). However, contralateral uninvolved eyes without CRVO did not show a significant change in CT over time (233.3 ± 87.9 versus 219.5 ± 90.6 µm; N = 71; P = .40). Persistent CME at final follow-up was associated with thicker baseline (277.6 ± 96.4 versus 235.1 ± 86.5 µm; P = .02) and final CT (265.7 ± 93.4 versus 215.0 ± 82.1 µm; P = .005). Change in CT was not related to change in BCVA ( P > .05). Conclusions: CT was greater in eyes with CRVO-related CME compared to eyes with CRVO but no CME and compared to uninvolved contralateral eyes. CT decreased in eyes with CRVO over time both among eyes that received intravitreal injections and among eyes that did not receive injections. CT may be a prognosticator of treatment response in CRVO-related CME.